Semiotic & Perception Of Way Finding Among Younger Consumers - Mahmud Zuhudi, Nurul Wahidah; Ahmed Ghazie, Diyana; Dolah, Jasni (2016)
The purpose of the research is aiming to recognize proper design systems of way finding in Malaysia. The idea is to determine the perceptions of younger consumers is associated with the multi-combinations design of way finding been applied in Malaysia now days, been affected with their demographic profiles or flexibility of psychology aspects due to their emotions and feeling and its connection with spatial space and environment. A survey in gaining perceptions based on the design differentiation of way finding was conducted among youngsters, resulted with many kind of clues, ideas and semiotic perspective of way finding and its improvement. It was associated with 100 younger consumers (20 aged – 25 years old). Participants been explained with the basic knowledge of way finding in Malaysia and responded with the question given. It resulted with a conclusion that there are many issues and critical concern related with our design system of way finding, 56 of young consumers claimed that its friendly user, give some suggestion that by using text and its application is suited to enhance meaning of way finding in Malaysia. Furthermore, the improvement of the systems will be able to increase the good feelings of peoples. Association of 100 young consumers (male: 28, female=72) were been asked to respond on survey questions, they been exposed with different design systems of way finding in Malaysia and assortment of perceptions been gathered. The practicality of semiotic knowledge, beneficial impact of it, in relation with cognitive mapping been performed during the session. Findings revealed with many kinds of clues on the way their doing an interpretation of design system of way finding in Malaysia. The crucial impacts gathered is directly coming from the approach of way finding been applied, resulted with 56 participants claimed that the way finding design system is friendly user, contributed to relevant recommendation to use text and its application to perceive meaning of location and direction, proven by 35 participants out of 100. Significantly, the research will indicate many kinds of good perceptions on the usage of semiotics understanding with relevant way finding in Malaysia. By having a helpful and identification signage design systems, it’s able to reduce frustrated feelings, confusions, tiredness, stress, and illness and save times during navigating to preferable location